PENGARUH MEDIA PEMBELAJARAN ASSEMBLR EDU TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATERI BAGIAN TUBUH TUMBUHAN DAN FUNGSINYA KELAS IV SD - Kamaliah, Lutfiyatul; Satianingsih, Rarasaning (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether there is an effect of Assemblr Edu learning media on critical thinking skills on the material of plant body parts and their functions in grade 4 SD. Assemblr Edu is an application that provides three-dimensional work features and is based on Augmented Reality (AR). The research used a quantitative approach with the type of research Quasi Experimental Design using Nonequivalent Control Group Desaign. The research was conducted at SDN Keboananom, the sample was selected by purposive sampling in class four A experiment and four C control class. Data collection techniques through instrument tests on critical thinking indicators. Data analysis used independent sample t-test after conducting prerequisite tests, namely normality and homogeneity tests. The results showed a significant effect of Assemblr Edu learning media on critical thinking skills on the material of plant body parts and their functions in grade four elementary schools. For future researchers, it is recommended to further explore the use of technology-based learning media in a broader learning context.